2019
DOI: 10.46586/tches.v2020.i1.203-230
|View full text |Cite
|
Sign up to set email alerts
|

Improved Heuristics for Short Linear Programs

Abstract: In this article, we propose new heuristics for minimising the amount of XOR gates required to compute a system of linear equations in GF(2). We first revisit the well known Boyar-Peralta strategy and argue that a proper randomisation process during the selection phases can lead to great improvements. We then propose new selection criteria and explain their rationale. Our new methods outperform state-of-the-art algorithms such as Paar or Boyar-Peralta (or open synthesis tools such as Yosys) when tested on rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…In 2019, Li et al (34) focused on the construction of involutory MDS matrices and modified Boyar's SLP [26,47] by considering the circuit depth metric. In 2019, Tan and Peyrin (54) proposed new heuristics called Randomized Normal Boyar Peralta (RNBP) and two nondeterministic A1 and A2 algorithms. Liu et al, (55) proposed a new heuristic based on forward and backward searching by considering low-latency criteria.…”
Section: Local Optimization and Global Optimization Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2019, Li et al (34) focused on the construction of involutory MDS matrices and modified Boyar's SLP [26,47] by considering the circuit depth metric. In 2019, Tan and Peyrin (54) proposed new heuristics called Randomized Normal Boyar Peralta (RNBP) and two nondeterministic A1 and A2 algorithms. Liu et al, (55) proposed a new heuristic based on forward and backward searching by considering low-latency criteria.…”
Section: Local Optimization and Global Optimization Techniquesmentioning
confidence: 99%
“…On the other hand, open synthesis tools provide efficient circuits, but they have some limitations (54). LIGHTER (14) and SAT-based tools (56) find efficient or even optimal (under some assumptions) circuits for small dimensions but their heuristics do not provide good circuits for larger dimensions.…”
Section: Local Optimization and Global Optimization Techniquesmentioning
confidence: 99%
“… Boyar, Find & Peralta (2019) proposed a new heuristic creating smaller linear and nonlinear circuits for a given circuit depth bound. Tan & Peyrin (2019) proposed Randomized Normal Boyar Peralta (RNBP) heuristic and two non-deterministic algorithms A1 and A2. All these given heuristics focus on the reduction of XOR counts by using temporary intermediate signals (gates) to determine the globally optimized implementations of a diffusion matrix.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, they converted circuits constructed using only two-input gates into new ones with a combination of two-input and three-input XOR gates. Then, Baksi et al (2021) introduced enhanced versions of BP heuristic (originally presented in Boyar & Peralta (2010) and Tan & Peyrin (2019) ), simply called BDKCI. These improved versions support two-input, three-input, and four-input XOR gates.…”
Section: Introductionmentioning
confidence: 99%
“…In 2017 [14], Kranz et al showed that the AES MixColumns matrix is implemented with only 97 xor gates by using BP algorithm [8]. Furthermore, many other variants of the BP algorithm are proposed in [3,23,24]. Recently, a quite different heuristic based on the decomposition of a matrix was proposed in [26], which provided an implementation circuit of the AES MixColumns matrix with remarkably, 92 xor gates.…”
Section: Introductionmentioning
confidence: 99%